The somatic phraseology in the colloquial speech of the central region of Cuba (Islas, 2023)
Introduction: The present article is framed within the studies of somatic phraseology, through the analysis of a corpus of 166 locutions that reflect notions about human experience and the interaction between speakers in the midst of the reality that surrounds and determines them.Methods: 166 locutions with somatic elements related to the head are analyzed following the classification of Mellado Blanco (2000). A descriptive approach is applied to examine their behavior in the realization or not of concrete physical actions, as well as the variety of somatic lexemes and their appearance in the sample.Results: The parts of the human body relative to the head that enable phraseological creativity and their relation to realizable physical actions and those phraseologically possible are analyzed.Conclusions: This research allows the knowledge of the phraseological flow, taking into account the existence of somatisms, and the semantic features that characterize it.
Keywords: phraseology; somatisms; locutions